Evaluation of Carboxymethyl Cellulose/Gelatin Hydrogel-Based Dressing Containing Cefdinir for Wound Healing Promotion in Animal Model - Zahra Soleimani; Hadi Baharifar; Najmeh Najmoddin; Kamyar Khoshnevisan (Gels)
The skin serves as a critical barrier against external pathogens, and its wound healing is a complex biological process that requires careful management to ensure optimal tissue regeneration. Hydrogels, a class of hydrophilic polymers, have emerged as promising materials for wound dressings due to their biocompatibility, biodegradability, and ability to create a moist wound environment conducive to cell proliferation and migration. In this research, a hydrogel dressing containing cefdinir (Cef) was made from a combination of carboxymethyl cellulose (CMC) and gelatin (Gel) by a physical crosslinking method, and their physicochemical, mechanical, and biological properties were investigated. Results show that the addition of Cef does not cause a significant change in the morphology or the tensile strength of the wound dressing. The swelling and degradation rate of the hydrogel slightly increased in the presence of Cef. The presence of Cef enhanced antibacterial effects up to 2.5-fold against P. aeruginosa (35 mm), S. aureus (36 mm), and S. pyogenes (35 mm). The results of the cytotoxicity test showed the absence of cytotoxicity in both drug-containing and drug-free wound dressings, as well as a survival rate of over 75% in cells after 48 h. The drug-containing wound dressing accelerates the formation of the epidermis layer and the production of fibroblast cells, and as a result, accelerates the wound healing process. The percentage of wound healing on the ninth day of treatment for an untreated wound was 30%, while this percentage was 40% with a wound dressing without medicine and 60% with a wound dressing containing medicine, and on the fifteenth day of treatment, the wound treated with both wound dressings had more than 85% healing. As a result, it is possible to use CMC/Gel hydrogel polymeric wound dressing containing Cef as a wound dressing for wound healing, according to the desired physicochemical properties and biocompatibility.